Nursing around the world: a perspective on growing concerns and the shortage of care - Vance DE (Dove Medical Press, 2011)
David E VanceThe University of Alabama School of Nursing, University of Alabama at Birmingham, Birmingham, AL, USAAbstract: Many of us think of nurses as people who provide direct care to us and our loved ones. And that is true. Images of a selfless person such as Florence Nightingale during the Crimean War running from one wounded soldier to another providing care inspires the imagination of what a nurse is and can be. Based on that image, a nurse is anyone who cares (and from a spiritual or philosophical perspective, that may be true). But nursing as a profession is so much more. nurse is someone with a very selective skill set that can only be developed and honed by intense training, education, and discipline while being used in a proscribed ethical manner. With such a combination of skills, ethics, and caring, nurses are the backbone of health care settings, tending to the individual needs of the patients; however, many nurses also function outside such traditional settings and perform numerous functions. Nurses are educators and provide data to the public designed to improve health literacy and promote physical and mental wellness. Nurses are computer and organizational specialists who provide hospitals and institutions with the technologies for keeping, maintaining, and analyzing records. Nurses are clergy, psychologists, and philosophers providing a direction and a moral compass in how to are for patients and each other. Nurses are researchers investigating everything from developing medication for Alzheimer's disease to improving crop yields to reduce hunger. Finally, nurses are advocates and leaders petitioning for justice and beneficence of all regardless of gender, age, race, religion, sexual orientation, and nationality; and as such, nursing is political and has a global impact. Nursing is global in nature and is facing global, as well as country specific, problems. The purpose of this editorial is to provide a brief overview of what some of these problems are. As such, questions and possible solutions are considered.Keywords: nursing shortage, aging, HIV, lifelong learning, exponential knowledge growth, limited resources, burnout